Economic Factors Influencing the Increase in Crime in North Sumatra Province in 2017-2022 - Qodaflaha Fika Alriefna (Majapahit Journal of Islamic Finance and Management, 2026)
Human behavior shaped by society is evil. Criminals usually break the law because they believe that the level of satisfaction they predict will be much higher than the satisfaction they will definitely receive from obeying the law or taking legal action. This research examines how GRDP, open unemployment rate, Gini ratio and number of poor people have an impact on crime in districts/cities of North Sumatra Province from 2017 to 2022. This analysis uses panel data regression. Chow and Hausman tests were used to process this research data. The research results show empirical evidence that the best estimation model is the Fixed Effect Model (FEM). The research results found that the open unemployment rate and Gini ratio had an effect on crime, while GRDP and the number of poor people had no effect on crime. Apart from that, the F test results of the four independent variables influence crime simultaneously. The results of calculating the coefficient of determination (R2), which shows an R2 value of 0.873983. This shows that GRDP, open unemployment rate, Gini ratio and number of poor people influence crime by 87.4%. Additional factors not discussed in this study had an impact of 12.6%.